FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN MENABUNG DI BANK SYARIAH (Studi Kasus Pada Bank Syariah Mandiri Cabang Jember) - Nurul Qomariah (Jurnal Ekonomi Akuntansi dan Manajemen, 2011)
This research is done to know the influence of variable of marketing mix service to the decision making of consumer to save their money in Bank in Jember. The independent variable in this research are the marketing mix that include: product (X1), price (X2), place (X3), promotion (X4)). The dependent variable in this research is the decision making of consumer. Research methode was with regresion analysis. The population was all the consumer that save their money in BSM Jember . The amount of sample was 50 respondent. Research was done by conducted direct observation to the the consumer that save their money in BSM Jember tough questioner. The technique of intake of sample used purposive random sampling. Based on the analysis result, it is obtained that the variable of marketing mix that have direct influence to the decision making of consumer The regresion coeficient of each variables was product (0,192), price (0,235) place (0,528) and promotion (0,242). Key Words : Marketing, product, price, place, promotion, purposive random sampling.